Assessing the impact of a change in the composition of public spending: a DSGE approach - Roland Straub; Ivan Tchakarov (European Central Bank (ECB), 2007)
Despite intense calls for safeguarding public investment in Europe, public investment expenditure, when measured in relation to GDP, has steadily fallen in the last three decades, evoking fears that economic activity may be correspondingly negatively affected. At the same time, however, public consumption in the EU-12 countries has trended up. In this paper, we provide a macroeconomic assessment of the observed change in the composition of public spending in the euro area in a medium-scale two-country dynamic stochastic general equilibrium (DSGE) model. First, we analyze the channels through which, both temporary and permanent public investment shocks generate larger fiscal multipliers than exogenous increases in public consumption. Furthermore, we quantify the negative impact of a change in fiscal stance, characterized by a permanent rise in public consumption and a permanent fall in public investment, keeping thereby the overall level of public spending constant. The key message of the paper is that calls for reversing the observed trend in the composition of public spending are well justifed.
Keywords: F41; F42; 330; DSGE models; euro area; Public consumption; Public investment; Öffentliche Investition; Öffentlicher Konsum; Dynamisches Gleichgewicht; Stochastischer Prozess; EU-Staaten